Importance of Standardization of Plant Materials –Critical to GMP: A Medisynth Perspective (Advancements in Homeopathic Research, 2022)
The standardization/testing of medicinal plant material is a matter of paramount concern in homoeopathic drug industry. Mother tincture prepared from plants can vary in quality and chemical constituent profile, if there are any variations in botanical materials. Standardization of herbal drug entails a process of prescribing a set of standards, constant parameters, definitive quality value that carry an assurance of quality, efficacy, safety and reproducibility of the finished products. It is a process of developing and agreeing upon technical standards. A significant factor which can add consistent quality to medicinal plants is satisfactory standardization. Acomplete array of authentication and evaluation tools can be utilized to provide a well-rounded scientific approach to the standardization of medicinal plant material. It is vital that the authenticity of plant material be established/tested using appropriate analytical tools before it is processed for making mother tincture. Theuse of homoeopathic medicine has increased tremendously over the past few decades.The quality control and standardization of medicinal plants is getting more attention in recent years since the commercialization of homoeopathic medicines has increased many folds.A wide range of methods can be applied for standardization/quality control of medicinal plants.Moreover,the Homoeopathic Pharmacopoeia of India (HPI) and other international pharmacopoeias propose organoleptic, macroscopic, microscopic, TLC, chemical and UV studies for standardization/quality control of homoeopathicmedicines. The Government of India has published 10 volumes of HPI and revision of monographs is also undertaken. This shows the commitment of the Government of India towards quality of homoeopathic medicines.
Keywords: standardization; medicinal plant material; homoeopathic drug industry; HPI